COMMUNICATE AND INFORM STUDENTS: CHALLENGES FOR THE UNIVERSITIES' COMMITMENT WITH IMPROVEMENT (Revista Electrónica Calidad en la Educación Superior, 2017)
This article presents a study made conducted in the framework of a self-evaluation process of the French Language Baccalaureate program at the Universidad de Costa Rica (UCR) in 2015.  The study was carried out by THE staff in charge of the self-evaluation process, and relied on the advice of the Center for Academic Evaluation. It examines the communication and information media or mechanisms that were most used by the students, in order to improve the communication of information related to the program. The results of the study suggest that young university students prefer more dynamic media, while the academic units tend to privilege other communication channels. This situation poses a challenge regarding the design of the communication strategies to be used to convey aspects of the quality assurance and continuous improvement plans of the university majors. A transition from unidirectional mass-communication schemes to more horizontal networking schemes is to be expected.